1993
DOI: 10.1161/01.cir.88.3.927
|View full text |Cite
|
Sign up to set email alerts
|

The ability of several short-term measures of RR variability to predict mortality after myocardial infarction.

Abstract: Background. We studied 715 patients 2 weeks after myocardial infarction to test the hypothesis that short-term power spectral measures of RR variability (calculated from 2 to 15 minutes of normal RR interval data) will predict all-cause mortality or arrhythmic death.Methods and Resuls.We performed power spectral analyses on the entire 24-hour RR interval time series. To compare with the 24-hour analyses, we selected short segments of ECG recordings from two time periods for analysis: 8 AM to 4 PM and midnight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
234
0
7

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(254 citation statements)
references
References 17 publications
13
234
0
7
Order By: Relevance
“…Besides their application in the assessment of cardiovascular autonomic function in diabetic patients, these new measures have been introduced in cardiology for risk stratification after myocardial infarction. Low HRV is associated with mortality risk in post-myocardial infarction patients [6,7] and also in the general population [8,9].…”
mentioning
confidence: 99%
“…Besides their application in the assessment of cardiovascular autonomic function in diabetic patients, these new measures have been introduced in cardiology for risk stratification after myocardial infarction. Low HRV is associated with mortality risk in post-myocardial infarction patients [6,7] and also in the general population [8,9].…”
mentioning
confidence: 99%
“…Correlation between spectral analysis of 24 h and short-term recordings is good (for most indicators there are given coefficients r > 0.75) (ref. 72 ).…”
Section: Reproducibility Of Hrv Measurementsmentioning
confidence: 99%
“…[72][73][74] ). The sensitivity of combination HRV with other risk factors is in the range of 29-58%, specificity up to 99% (ref.…”
Section: Reproducibility Of Hrv Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental stress-induced myocardial ischaemia during daily life activities is preceded by a decrease in HF-HRV suggesting parasympathetic withdrawal [13]. In addition, HRV-based indices of autonomic dysregulation are associated with the long-term risk of various cardiovascular disorders, including myocardial infarction and arrhythmias [14,15], although some negative studies have been reported as well (e.g., [16]). A reverse pathway is also well documented, such that myocardial ischaemia results in autonomic dysregulation [17].…”
Section: Introductionmentioning
confidence: 99%